Inhalable antibiotic resistomes emitted from hospitals: metagenomic insights into bacterial hosts, clinical relevance, and environmental risks - Wu, Dong; Jin, Ling; Xie, Jiawen; Liu, Hang; Zhao, Jue; Ye, Dan; Li, Xiang-dong (Microbiome, 2022)
Threats of antimicrobial resistance (AMR) to human health are on the rise worldwide. Airborne fine particulate matter (PM ), especially those emitted from hospitals, could serve as a substantial yet lesser-known environmental medium of inhalable antibiotic resistomes. A genome-centric understanding of the hosting bacterial taxa, mobility potential, and consequent risks of the resistomes is needed to reveal the health relevance of PM -associated AMR from clinical settings. Compared to urban ambient air PM , the hospital samples harbored nearly twice the abundance of antibiotic resistantance genes (ARGs, ~ 0.2 log (ARGs/16S rRNA gene)) in the summer and winter sampled. The profiled resistome was closely correlated with the human-source-influenced (~ 30% of the contribution) bacterial community (Procrustes test, P < 0.001), reflecting the potential antibiotic-resistant bacteria (PARB), such as the human commensals Staphylococcus spp. and Corynebacterium spp. Despite the reduced abundance and diversity of the assembled metagenomes from summer to winter, the high horizontal transfer potential of ARGs, such as the clinically relevant bla and bacA, in the human virulent PARB remained unaffected in the hospital air PM samples. The occurring patterns of β-lactam resistance genes and their hosting genomes in the studied hospital-emitting PM were closely related to the in-ward β-lactam-resistant infections (SEM, std = 0.62, P < 0.01). Featured with more abundant potentially virulent PARB (2.89 genome copies/m -air), the hospital samples had significantly higher resistome risk index scores than the urban ambient air samples, indicating that daily human exposure to virulent PARB via the inhalation of PM was ten times greater than from the ingestion of drinking water. The significance of AMR in the studied hospital-emitting PM was highlighted by the greater abundance of ARGs, the prevalence of potentially virulent PARB, and the close association with hospital in-ward β-lactam infections. A larger-scale multi-source comparison of genome-resolved antibiotic resistomes is needed to provide a more holistic understanding to evaluate the importance of airborne AMR from the "One-Health" perspective. Video Abstract.